(untitled) (Canadian Allergy & Immunology Today, 2022)
Investigation of immune function is essential for accurate diagnoses in patients with recurrent and/or unusual infections as well as those with features of immune dysregulation. Many new diagnostic tools have been added to our medical armamentarium in recent years yet the diagnosis of IEI still relies on the combination of clinical acumen to identify patients at risk, leading to appropriate laboratory and genetic tests. The early evaluation of immune function provides not only critical diagnostic information, but also guides clinical decisions regarding appropriate therapies and prevention of disease-associated morbidity and mortality. As illustrated in this article and by the clinical vignette, infection may not be the significant presenting feature for IEI. Patients for whom there are clinical suspicions for IEI should be evaluated with screening tests followed by directed protein/cellular and genetic testing. As this remains an evolving field, patients may need to be re-evaluated as our understanding progresses.